Between Ambition and Caution: Legal and Strategic Review of Government Decision-Making in Infrastructure Projects during Fiscal Crisis - Muh Aldian Maharani (AIBPM Publisher, 2025)
In regional fiscal policy, infrastructure projects are often proposed as long-term solutions to stimulate economic growth and regional development. However, when such projects are promoted under weak fiscal conditions amid declining local revenues and increasing expenditure pressures a strategic and ethical dilemma arises: should governments take the risk in pursuit of development ambition, or adopt a more cautious approach to maintain fiscal sustainability? This paper critically examines government decision-making on infrastructure projects during fiscal crises through legal and strategic policy analysis. Although such decisions may be legally valid, this study argues that there are normative boundaries and public responsibilities that must be upheld, including principles of fiscal prudence, efficiency, and social justice. When these boundaries are disregarded, policies may remain procedurally legal but substantively flawed. By integrating legal reasoning with policy reflection, this paper highlights the need for multidimensional risk evaluation including potential impacts on public services and poverty before such projects are executed. Without reform in governance and decision-making mechanisms, ambitious infrastructure initiatives risk undermining fiscal legitimacy and eroding public trust in regional government.